Analisis Pengaruh Inflasi, Tingkat Suku Bunga ( BI RATE ) Terhadap Indeks Harga Saham Gabungan di Indonesia - kartono, Dwi Intan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to determine the effect of inflation, interest rates (BI Rate) on the composite stock price index in Indonesia (IHSG). The data used is using empirical data by managing data that has been published by the Indonesian Stock Exchange (IDX), the Financial Services Authority (OJK) and Bank Indonesia (BI). Capital Market (capital market) is a liaison between investors and companies or government institutions through the trading of several long-term tradable financial products such as debt, stocks, mutual funds and derivative products. The actions related to the public offering and trading of securities are referred to as the capital market. Indonesia's general inflation rate rose to 3.55 percent (yoy) in May 2022, the highest since December 2017 and higher than the market estimate of 3.6 percent (yoy). The realization of inflation in May 2022, which was lower than the previous month, was evenly distributed in all regions, Bank Indonesia raised the benchmark interest rate and cut the balance sheet to overcome inflation. The increase in the benchmark interest rate will be a negative sentiment in the stock market. High interest rates will make the expansion costs of issuers more expensive so that profits will be eroded so that the JCI also weakens, the increase in the benchmark interest rate has an impact on banking issuers due to the fall in profit margins in April the benchmark interest rate rose by 50 bps to 0.75-1% . The market estimates that the Faderal Funds Rate will increase by 7 times in 2022. In general, there is a positive relationship between economic growth and the development of stock prices. But after the monetary crisis hit Indonesia, things were not like that. In the second quarter of 1999 when the value of GDP decreased, stock prices actually rose sharply. This can be seen from the JCI value reaching 662.02 The JCI also experienced a sharp increase at the end of the 4th quarter of 1999, while the GDP value showed a decline.Keywords: Inflation, Interest Rates, IHSG.